2005
DOI: 10.1073/pnas.0508042102
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic engineering at an interface between large and small subunits imparts land-plant kinetic properties to algal Rubisco

Abstract: Ribulose-1,5-bisphosphate carboxylase͞oxygenase (Rubisco) catalyzes the rate-limiting step of photosynthetic CO 2 fixation and, thus, limits agricultural productivity. However, Rubisco enzymes from different species have different catalytic constants. If the structural basis for such differences were known, a rationale could be developed for genetically engineering an improved enzyme. Residues at the bottom of the large-subunit ␣͞␤-barrel active site of Rubisco from the green alga Chlamydomonas reinhardtii (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
107
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 48 publications
2
107
0
2
Order By: Relevance
“…3) (24,29,30) contrasts with the recent success in shaping rice rubisco toward C 4 -like catalysis using heterologous S-subunits from C 4 sorghum (16). Similarly, structural changes to the S-subunit have improved Chlamydomonas rubisco catalysis (17). As highlighted recently (20), differences in rubisco S-subunit sequence also may account for the catalytic deviation of Flaveria palmeri rubisco, whose L-subunit sequence matches that of tob flo-bid (coding 309 Ile) but shows C 3 catalysis.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…3) (24,29,30) contrasts with the recent success in shaping rice rubisco toward C 4 -like catalysis using heterologous S-subunits from C 4 sorghum (16). Similarly, structural changes to the S-subunit have improved Chlamydomonas rubisco catalysis (17). As highlighted recently (20), differences in rubisco S-subunit sequence also may account for the catalytic deviation of Flaveria palmeri rubisco, whose L-subunit sequence matches that of tob flo-bid (coding 309 Ile) but shows C 3 catalysis.…”
Section: Discussionmentioning
confidence: 65%
“…The catalytic core of L 8 S 8 rubisco comprises four 52-kDa large (L)-subunit pairs which are capped by two sets of 15-kDa small (S)-subunit tetramers that provide structural stability and influence catalysis (16,17). Although supplementing rice rubisco with Ssubunits from the C 4 plant sorghum was found to improve V C of the heterologous L 8 S 8 enzyme (16), crosses between C 3 and C 4 Flaveria and Atriplex species showed C 4 catalysis to be maternally inherited (18,19) and hence defined by the chloroplast-encoded L-subunit gene (rbcL).…”
mentioning
confidence: 99%
“…Whereas adaptive mutations 10-20 Å from active sites have occasionally been identified in other enzymes (31), in RubisCO, these form the majority of positively selected sites that distinguish C 3 and C 4 species. Experiments with RubisCO from the green alga Chlamydomonas reinhardii previously implicated the interfaces between large and small subunits in the modulation of catalytic rates (32). The analysis here increases the number of known functionally significant intersubunit sites (Table S2) and demonstrates a link with the C 3 -C 4 transitions in flowering plants.…”
Section: Discussionmentioning
confidence: 75%
“…Directed mutagenesis of Rubisco from the cyanobacterium Synechococcus expressed in Escherichia coli and directed mutagenesis and genetic selection in vivo in the green alga Chlamydomonas reinhardtii have identified several residues of the small subunit that can influence ⍀ (17-21). When the longer loop between ␤-strands A and B of the Chlamydomonas small subunit was replaced with the shorter loop of Synechococcus, a decrease in ⍀ was observed (15,22 …”
mentioning
confidence: 99%
“…However, some plant and algal species contain CO 2 -concentrating mechanisms (CCMs) (reviewed in Refs. 10 -14), which make it difficult to tell whether any Rubisco enzyme in nature is better than any other with respect to the CO 2 and O 2 concentrations (and temperatures) that the enzyme encounters in vivo (1,15). Nonetheless, various mutant substitutions have been identified that can influence ⍀ (reviewed in Refs.…”
mentioning
confidence: 99%